The development and social function of digital art museum - Tianwei Xiao; Zaimie Sahibil (Manson Publish Group, 2020)
The innovation and application of digital technology have affected the development direction and trend of future construction of art museums. The rise of digital art museums has expanded the knowledge dissemination channels of art museums and the ways of displaying works, giving the public a new way of viewing exhibitions and artistic experience. This paper analyzes the application and status quo of Digital Art Museum, studies the social function and social significance of Digital Art Museum in the information age, discusses the construction mode and operation mechanism of Digital Art Museum, and analyzes the advantages and problems in the construction of Digital Art Museum.